2023
DOI: 10.3390/nu15081931
|View full text |Cite
|
Sign up to set email alerts
|

Oral intake of Lactiplantibacillus pentosus LPG1 Produces a Beneficial Regulation of Gut Microbiota in Healthy Persons: A Randomised, Placebo-Controlled, Single-Blind Trial

Abstract: The search for vegetable-origin probiotic microorganisms is a recent area of interest. This study conducted a phase I clinical trial to assess the effects of oral administration of Lactiplantibacillus pentosus LPG1, a natural strain with probiotic potential isolated from table olive fermentations, on the gut microbiota. The trial was a randomised, placebo-controlled, single-blind study involving 39 healthy volunteers. Group A (n = 20) ingested one capsule/day of L. pentosus LPG1 containing 1 × 1010 UFC/capsule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This holds great importance given the probiotic potential presented by this specific strain of Lpb. pentosus ( Benítez-Cabello et al, 2019 , 2020 ; López-García et al, 2023b ). Therefore, LPG1 needs to express genes encoding surface adhesion proteins, as observed in previous studies on diverse Lpb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This holds great importance given the probiotic potential presented by this specific strain of Lpb. pentosus ( Benítez-Cabello et al, 2019 , 2020 ; López-García et al, 2023b ). Therefore, LPG1 needs to express genes encoding surface adhesion proteins, as observed in previous studies on diverse Lpb.…”
Section: Resultsmentioning
confidence: 99%
“…This microorganism has also shown important potential probiotic features, proving to be an anti-inflammatory agent, reduce cholesterol levels, inhibit foodborne pathogens, and adhere to Caco−2 cells ( Benítez-Cabello et al, 2019 , 2020 ). Moreover, LPG1 has recently shown the capacity to modulate the intestinal microbiota of healthy individuals ( López-García et al, 2023b ).…”
Section: Introductionmentioning
confidence: 99%
“…Complete details of the clinical trial conducted in the present work can be found in López-García et al [ 15 ]. This study followed the Declaration of Helsinki and was conducted at the Maimónides Biomedical Research Institute (IMIBIC, Cordoba, Spain) and the Reina Sofía University Hospital (Cordoba, Spain) between July and September 2021.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 39 healthy volunteers from Seville ( n = 6) and Córdoba ( n = 33) provinces (Andalusian, Spain) fulfilled the inclusion and exclusion criteria and were selected to participate in this study. Participants’ inclusion and exclusion criteria, baseline clinical parameters, and the participants’ metabolic and lipid profiles can be consulted in López-García et al [ 15 ]. Descriptive statistics analysis for sex, age, and weight variables of the 39 selected volunteers are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation